Eco-Interlocking Paving Block (Eco-IPB) by using LDPE/Sand Blends - Bachok, Muhammad Halim; Tuan Ismail, Tuan Noor Hasanah; Yahya, Nur Faezah; Hanipah, Mohd Hafizal; Sarimin, Muhamad Khairul Fitri; Kasalan, As’shar (Journal of Advanced Industrial Technology and Application, 2020)
Bitumen and interlocking paving blocks are the common materials used in the construction of flexible road pavements in Malaysia and other developing countries. In the last few years, more focus has been paid to the interlocking paving block when dealing with the area that less durability because of certain environmental and organizational limitations. Nonetheless, cement has been used as a bonding agent in the conventional concrete interlocking paving block (CIPB) and has a detrimental effect on the environment. This research was therefore conducted to examine the alternative paving block by substituting cement content with plastic wastes, it has called as an Eco-interlocking paving block (Eco-IPB). The aim of this research is to produce a sustainable, lightweight, stiff and cost-effective product. In this research, the Eco-IPB was prepared in four different LDPE/sand blends of 1:1, 1:2, 1:3 and 1:4. The thermal analysis and physical tests were conducted to determine temperature effect and physical performance of plastic bags. The performance of Eco-IPB was evaluated with regard to the density measurement, water absorption and compression test. The findings show that the optimum LDPE/sand ratio of Eco-IPB of LDPE was 1:2 based on the high compressive strength of 20.80 MPa had been achieved. Moreover, the widespread use of plastic waste as an alternative construction material will help reduce plastic residues and promote green technology.